Germany’s "Excellence Initiative" - Fallon, Daniel (International Higher Education, 2008)
In January 2004, German federal minister for higher education and research in the Social Democratic government started a process called the Excellence Initiative, which simply selects and supports six universities to be Germany's top institutions of higher learning, with an intensive finance from the federal and state governments. Three competitions were organized for the initiative: graduate schools, excellence clusters, and futures concept. The Excellence Initiative has been breaking the previous notion of the equivalence of universities, in order to maintain international competitiveness of German higher education.